Literasi keuangan syariah dan transformasi digital: Analisis Perilaku Gen Z dalam pengunaan fintech - Mustika, Rika; Sudirman, Iman Fauzi; Burhani, Han Han (Journal of Accounting and Digital Finance, 2025)
This study aimed to analyze the influence of Islamic financial literacy and digital transformation on Generation Z’s behavior in utilizing Sharia-based financial technology. The research addressed the issue of low Islamic financial literacy levels among young people despite their widespread adoption of digital technologies. A quantitative approach was employed, using survey data from 71 respondents who actively used digital financial services. Multiple linear regression analysis was applied to examine the two independent variables’ partial and simultaneous effects on the dependent variable. The results indicated that Islamic financial literacy positively and significantly influenced the behavior of using financial technology. In contrast, digital transformation did not show a significant partial effect, although both variables significantly impacted Generation Z’s financial behavior. The study concluded that strengthening Islamic financial literacy is essential for shaping responsible financial behavior aligned with Islamic principles.